THE IMPLEMENTATION OF KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) IN THE TEACHING OF ENGLISH; A DESCRIPTIVE STUDY IN THE TENTH GRADE OF SMA NEGERI 1 NGUNUT, 2013/2014 ACADEMIC YEAR - Anis Azimah (JARES (Journal of Academic Research and Sciences), 2016)
The objective of this study is to describe the teachers ’ perceptions towards the implementation of Kurikulum Tingkat Satuan Penddikan (KTSP) in SMA Negeri 1 Ngunut and also the implementation of Kurikulum Tingkat Satuan Pendidikan (KTSP) in the Teaching of English in the classroom for the tenth grade students of SMA Negeri 1 Ngunut 2013/2014 academic year, including its material, teaching learning activity and the evaluation. Further more, it is also intended to know more about the strengths and the weaknesses of the implementation of Kurikulum Tingkat Satuan Pendidikan (KTSP). In this research, the writer uses a qualitative research. To describe the students ’ and teachers ’ perception towards the implementation of Kurikulum Tingkat Satuan Pendidikan (KTSP) in the class, the researcher uses descriptive method. The technique of collecting the data in this research is unobtrusive observation, in-depth interviewing, and document analysis. The writer uses guided-interview to support the data. In analyzing the data, the writer uses interactive analysis method by data reduction, data display, and conclusion drawing. After doing observation and interview, the writer can conclude that the teachers have good perception towards the implementation of KTSP in the school and play their role as teachers in the classroom well. The implementation of Kurikulum Tingkat Satuan Pendidikan (KTSP) in the teaching of English at the tenth grade of SMA Negeri 1 Ngunut is well conducted. The teaching-learning activity in the classroom runs well because the teachers always try to encourage the students in teaching-learning process. The material given to the students in teaching-learning activity is appropriate to the KTSP ’s standard material. Key words: Implementation, Kurikulum Tingkat Satuan Pendidikan (KTSP), Received: 23 June, 2016; Accepted: 8 September, 2016